2015
DOI: 10.1007/s00284-015-0909-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Concentration Methods for the Molecular Detection of Enteroviruses in Raw and Treated Sewage

Abstract: Human enteric viruses are a major causative agent of emerging waterborne diseases and constitute a serious public health concern. Environmental contamination occurs through discharge of waste materials from infected persons. Methods for viral detection should be developed to detect low infective dose of enteric viruses in environment. In this study, we aimed at comparing two concentration methods for the detection of naturally occurring enteroviruses in raw and treated sewage. In the first method, polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although in our study it is indicated that the rotavirus removal is not complete in the effluent of WWTPs, the virus pollution has been significant and revealed a critical public health danger. This result is an agreement with the result of previous studies that display the presence of rotaviruses not only in sewage raw but also in treated wastewater [4,11,19,26]. Studies conducted to evaluate the efficacy of wastewater treatment plants in developing countries are limited to bacterial indicators such as coliforms, while viruses are ignored.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although in our study it is indicated that the rotavirus removal is not complete in the effluent of WWTPs, the virus pollution has been significant and revealed a critical public health danger. This result is an agreement with the result of previous studies that display the presence of rotaviruses not only in sewage raw but also in treated wastewater [4,11,19,26]. Studies conducted to evaluate the efficacy of wastewater treatment plants in developing countries are limited to bacterial indicators such as coliforms, while viruses are ignored.…”
Section: Discussionsupporting
confidence: 91%
“…The stools of infected people contain many enteric viruses, usually 10 5 -10 11 virus particles/g stool, meaning the contamination of different types of environmental water samples like river, groundwater, seawater, and drinking water. Several viruses, such as norovirus, rotavirus, adenovirus, astrovirus, and sapovirus, are responsible for gastroenteritis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no method is completely perfect by taking into account the principle and procedure of each method. For instance, the detection of pathogenic viruses is obtained in a disinfection procedure, but this method is not suitable for the detection of coliform bacteria due to low concentration of bacteria indicator [167]. The generation of DNA-based amplification method has evolved due to demands in producing combined method of detection with higher specificity and rapidity.…”
Section: Membrane Filtration (Mf) Methodsmentioning
confidence: 99%
“…Initially, the model-based event detection method involves a signal-to-noise principles using laboratory and sensor test-loop evaluation. Indication of contamination events is derived from the chemical changes in background water quality signals [88,89], [137][138][139][140][141][142][143], [163], [167], [217], [244,245], [429,430] Sensor Placements Approach [372][373][374][375][376][377], [380][381][382][383][384][385][386][387][388], [391], [400][401][402][403][404][405][406][407], [434][435][436][437][438] Event Detection Model-based -High true positive alarm rate -Low false alarm detections -Fast response time -Complicated calibration process -Highly dependable on predictions and estimations -Computationally intensive…”
Section: Algorithmic Model-based Event Detectionmentioning
confidence: 99%